A Brief Note on the Validity and Reliability of the Rating of Perceived Exertion Scale in Monitoring Exercise Intensity among Chinese Older Adults in Hong Kong. Issue 3 (December 2015) - Chung, Pak-Kwong; Zhao, Yanan; Liu, Jing-Dong; Quach, Binh
This study examined the validity and reliability of the Cantonese Borg 6–20 Rating of Perceived Exertion (RPE) scale in monitoring exercise intensity among Chinese older adults. A total of 40 apparently healthy older adults (16 men, 24 women; M age = 69.8yr., SD = 4.56) performed two trials of three intermittent exercise tests administered in random order using the cycle ergometer. Results revealed significant differences of RPE, HR, and VO2 between different workloads, and there were moderate to high correlations between RPE and HR and VO2, respectively. Results also found moderate consistency of RPE between Trial 1 and Trial 2. These indicated that the Cantonese 6–20 RPE scale can be used as a valid and reliable tool for monitoring exercise intensity among the Chinese older adults.